Development of a non-pulsating buck-boost converter with continuous current mode (CCM) - Zakaria, Mohd Sharif (2013)
This master report presents a voltage tracking of dc-dc buck-boost converter. The dcdc Buck converter is designed to tracking the output voltage with three mode of operation. This master report consists open loop control, closed loop control with PID controller. The Buck-Boost converter has some advantages compare to the others type of dc converter. However the nonlinearity of the dc-dc Buck-Boost converter characteristics, cause it is difficult to handle by using conventional method such as open loop control system.. In order to overcome this main problem, a close loop control system using proportional-integral-differential (PID) controller is developed. The effectiveness of the proposed method is verified by develop simulation model in MATLAB-Simulink program. The simulation results show that the proposed proportional-integral-differential (PID) controller produce significant improvement control performance compare to convational converter for voltage tracking output for dc-dc Buck-Boost converter.